Setup and Validation of Flow Cell Systems for Biofouling Simulation in Industrial Settings. (26th April 2012) - Teodósio, Joana S.; Simões, Manuel; Alves, Manuel A.; Melo, Luís F.; Mergulhão, Filipe J.
Abstract : A biofouling simulation system consisting of a flow cell and a recirculation tank was used. The fluid circulates at a flow rate of 350 L⋅ h −1 in a semicircular flow cell with hydraulic diameter of 18.3 mm, corresponding to an average velocity of 0.275 m⋅ s −1 . Using computational fluid dynamics for flow simulation, an average wall shear stress of 0.4 Pa was predicted. The validity of the numerical simulations was visually confirmed by inorganic deposit formation (using kaolin particles) and also by direct observation of pathlines of tracer PVC particles using streak photography. Furthermore, the validity of chemostat assumptions was verified by residence time analysis. The system was used to assess the influence of the dilution rate on biofilm formation by Escherichia coli JM109(DE3). Two dilution rates of 0.013 and 0.0043 h − 1 were tested and the results show that the planktonic cell concentration is increased at the lower dilution rate and that no significant changes were detected on the amount of biofilm formed in both conditions.